Fine Ash‐Bearing Particles as a Major Aerosol Component in Biomass Burning Smoke. Issue 2 (18th January 2022) - Adachi, Kouji; Dibb, Jack E.; Scheuer, Eric; Katich, Joseph M.; Schwarz, Joshua P.; Perring, Anne E.; Mediavilla, Braden; Guo, Hongyu; Campuzano‐Jost, Pedro; Jimenez, Jose L.; Crawford, James; Soja, Amber J.; et al.
Abstract: Biomass burning (BB) events are occurring globally with increasing frequency, and their emissions are having more impacts on human health and climate. Large ash particles are recognized as a BB product with major influences on soil and water environments. However, fine‐ash particles, which have diameters smaller than several microns and characteristic morphologies and compositions (mainly Ca and Mg carbonates), have not yet been explicitly considered as a major BB aerosol component either in field observations or climate models. This study measured BB aerosol samples using transmission electron microscopy (TEM) and ion chromatography during the Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ) campaign. We show that significant amounts of fine ash‐bearing particles are transported >100 km from their fire sources. Our environmental chamber experiments suggest that they can act as cloud condensation and ice nuclei. We also found considerable amounts of fine ash‐bearing particles in the TEM samples collected during previous campaigns (Biomass Burning Observation Project and Megacity Initiative: Local and Global Research Observations). These ash particles are commonly mixed with organic matter and make up ∼8% and 5% of BB smoke by number and mass, respectively, in samples collected during the FIREX‐AQ campaign. The measured ash‐mass concentrations are approximately five times and six times greater than those of BB black carbon and potassium, respectively, scaling to an estimated global emission of 11.6 Tg yr −1 with a range of 8.8–16.3 Tg yr −1 . Better characterization and constraints on these fine ash‐bearing particles will improve BB aerosol measurements and strengthen assessments of BB impacts on human health and climate. Plain Language Summary: Biomass burning (BB) events occur globally and impact climate and human health. Ash particles larger than ∼10 μm are well known as the main products of BB that contaminate the soil and water near the source regions. On the other hand, ash particles having diameters smaller than several microns, which are inhalable and can be transported long distances, are not yet recognized as a major aerosol component of BB smoke. This study reveals that such fine ash‐bearing particles are abundant in number (∼8%) and mass (∼5%) within BB smoke. The global emission of fine ash particles is estimated to be 11.6 Tg yr −1 with a range of 8.8–16.3 Tg yr −1 . By considering their abundance and properties, we will strengthen assessments of BB impacts on human health and climate. Key Points: Ash‐bearing particles with diameters smaller than several microns can be one of the major aerosol components in biomass burning (BB) smoke Fine ash‐bearing particles can act as cloud condensation or ice nuclei and influence cloud properties The global emission of fine ash aerosol mass from BB is estimated to be ∼11.6 Tg yr −1